The Dilemmas of African-American Orientalism: Coltrane and the Hispanic Imaginary in ‘Olé’ - Parent, Emmanuel; Tosser, Grégoire (Jazz Research Journal, 2010)
Through the analysis of John Coltrane’s‘Olé’, this paper examines the artist’s treatment of the Hispanic imaginary with musicological aspects as well as anthropological considerations, and suggests that the work lies within a double framework. The first framework is African-American, with the multiplication of works of jazz that has mobilized the Spanish musical universe since the mid-fifties. The second is European, with the long Western tradition of Spanish orientalism that flourished in the XIXth century. The central purpose will thus be to examine what type of Orientalism Coltrane suggests to us. In their confrontation with the Hispanic imaginary, do Coltrane and his musicians attempt to foreground roots or otherness, empathy or conflict? Despite a genuine experimental treatment that allows him to transcend a mere Spanish exoticism, and a commitment to the politics of Black cultural nationalism in the 1960’s, we argue that Coltrane’s brand of orientalism is not that different from his European avant-garde counterparts’. In other words, John Coltrane does not totally get rid of a common staple element in classical Orientalism: the essentialisation of pre-modern cultures.